Ionic Liquid-assisted Separation of Carbohydrates from Lignocellulosic Biomass - Huyen Thanh Vo; Kim, Chang Soo; Lee, Sang Deuk; Lee, Hyunjoo (대한화학회, 2016)
To utilize carbohydrates in lignocellulosic biomass, a fractionation of lignocellulose is crucial. In this study, poplar wood sawdust was treated with a mixture of ionic liquids, 1-butyl-3-methylimidazolium acetate ([Bmim][OAc]) and 1,3-dimethylimidazolium methyl phosphite ([Dmim][MeO(H)PO2]), to separate carbohydrate and lignin components from wood. Three types of product were isolated: water-soluble wood (WSW), water-insoluble wood (WIW), and wood in ionic liquids (WIL). At a dissolution temperature of 130 degrees C for 18 h, WSW was found to have high carbohydrate and low lignin contents of 81.0 and 3.5%, respectively, corresponding to a delignification efficiency of 88.9%. WIW isolated under the same condition was found to have 55% of the lignin of native poplar. However, with an increase in the dissolution temperature and the time, the yield of WIL increased due to the increased phosphorylation in both carbohydrate and lignin, forming a mixture of carbohydrate and lignin having phosphorylated ionic functional groups.